Interfaith dialogue and the role of mosque: a case study of Klang valley’s mosques - Abdullah, Fatimah; Bahari, Che Amnah (2016)
Today interfaith dialogue is a necessity. Personal culture is translated into social culture and eventually there is no longer a homogeneous culture but develop to be heterogeneous or global culture. It is necessary for nations to participate and to be involved through dialogue in making that global culture and identity in line with their religious conviction. Indeed, interfaith dialogue is a complex matter and if not properly handled will lead to atrocity between the followers of different religions. This writing intends to study the premises and etiquette for interfaith dialogue and how mosques particularly in Klang Valley contribute to its awareness. The method employed is to examine the speeches from 5 selected mosques; programs organized and interview with the committee members by 10 selected mosques and 200 questionnaire surveys from 20 mosques.